2012
DOI: 10.1159/000336991
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Inflammation: Chronic Pancreatitis as a Risk Factor of Pancreatic Cancer

Abstract: Pancreatic carcinoma is a condition with late diagnosis and one for which there is no effective screening method. One possible diagnostic approach of so-called early adenocarcinoma is the identification and systematic examination of individuals at risk for this condition. Between 1992 and 2005 we systematically observed 223 individuals diagnosed with chronic pancreatitis. In this 14-year period we performed classical biochemical tests, endoscopic ultrasound, CT scans and ERCP. We also asked about the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 76 publications
(42 reference statements)
1
33
1
2
Order By: Relevance
“…Of those, 71.8% had chronic alcoholic pancreatitis. Systematic follow-up of chronic pancreatitis patients [136] may help track the transformation of chronic pancreatitis to pancreatic carcinoma. Among patients with hereditary pancreatitis, 20% were found to have pancreatic carcinoma during autopsy.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…Of those, 71.8% had chronic alcoholic pancreatitis. Systematic follow-up of chronic pancreatitis patients [136] may help track the transformation of chronic pancreatitis to pancreatic carcinoma. Among patients with hereditary pancreatitis, 20% were found to have pancreatic carcinoma during autopsy.…”
Section: Chronic Pancreatitismentioning
confidence: 99%
“…With respect to PC specifically, chronic pancreatitis may also be a risk factor [10]. It is likely that many of these factors contribute cumulatively to risk over years, given that PC (or any cancer) does not spontaneously appear within the body.…”
Section: Introductionmentioning
confidence: 99%
“…2 Because pancreatic cancer is most often diagnosed at a late stage, prognosis is poor with 1-year survival rates of 20% and 5-year survival rates of only 4-5%. 2,3 Several risk factors have been consistently associated with the risk of developing pancreatic cancer, including family history of pancreatic cancer, 4 chronic pancreatitis, 5 cigarette smoking, 6 diabetes mellitus 7 and obesity. 8 According to the 2012 WCRF/AIRC expert report, evidence for the relation between vegetable and fruit consumption and pancreatic cancer risk is limited and inconsistent, 9 with inverse associations found in case-control studies and no associations found in cohort studies.…”
mentioning
confidence: 99%